Melatonin versus Zinc for Sleep Disorders in Cirrhotic Patients: A Randomized Double-Blind Pilot Trial: Melatonin or zinc in sleep disorders of cirrhosis - Hatami, Behzad; Payvandi, Dorsa; Abbasinazari, Mohammad; Sadatsafavi, Seyed-Mehregan (Iranian Journal of Pharmaceutical Sciences, 2026)
Given the absence of an established gold standard for managing sleep disturbances in patients with cirrhosis, the present randomized double-blind trial was conducted to evaluate the efficacy and safety of melatonin (5 mg/night) versus zinc (50 mg/night) in alleviating sleep disorders within this population. A total of 42 eligible participants were enrolled and randomly assigned to receive either melatonin or zinc. The Pittsburgh Sleep Quality Index (PSQI) was evaluated at baseline and again after one month of treatment. All participants tolerated the interventions well, and no dropouts occurred during the study period. Statistical analysis revealed that PSQI scores significantly improved in both treatment groups compared with baseline (p = 0.001 for both the melatonin and zinc groups). However, there was no statistically significant difference between the two interventions in PSQI scores at the end of the trial (p = 0.936). Based on the observed efficacy and tolerability, both melatonin at 5 mg nightly and zinc at 50 mg nightly may be considered as viable options for addressing sleep disorders in individuals with cirrhosis.